2021
DOI: 10.3390/nano11051231
|View full text |Cite
|
Sign up to set email alerts
|

Specific Absorption Rate Dependency on the Co2+ Distribution and Magnetic Properties in CoxMn1-xFe2O4 Nanoparticles

Abstract: Mixed ferrite nanoparticles with compositions CoxMn1-xFe2O4 (x = 0, 0.2, 0.4, 0.6, 0.8, and 1.0) were synthesized by a simple chemical co-precipitation method. The structure and morphology of the nanoparticles were obtained by X-ray diffraction (XRD), transmission electron microscope (TEM), Raman spectroscopy, and Mössbauer spectroscopy. The average crystallite sizes decreased with increasing x, starting with 34.9 ± 0.6 nm for MnFe2O4 (x = 0) and ending with 15.0 ± 0.3 nm for CoFe2O4 (x = 1.0). TEM images show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
1
21
0
2
Order By: Relevance
“…In the calorimetric method, the temperature rise of magnetic nanoparticles was recorded over a specific interval of time under an AMF with a specific strength and frequency [47], and the results are shown in figures 9(a)-(c). The SAR values of all samples are evaluated from the linear part of the slope using the following equation [24] :…”
Section: Sar Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the calorimetric method, the temperature rise of magnetic nanoparticles was recorded over a specific interval of time under an AMF with a specific strength and frequency [47], and the results are shown in figures 9(a)-(c). The SAR values of all samples are evaluated from the linear part of the slope using the following equation [24] :…”
Section: Sar Analysismentioning
confidence: 99%
“…The amount of thermal energy dissipated in hyperthermia applications is determined by measuring the specific absorption rate (SAR). The SAR is the ratio of the thermal power dissipation to the mass of the magnetic nanoparticles, and is influenced by the particle size, saturation magnetization, magnetic anisotropy [23], applied strength, and frequency of the AMF [19,24]. Research on hyperthermia therapy has also generated interest for encapsulating magnetic nanoparticles with nonmagnetic materials to serve as heating mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt ferrite nanoparticles (13.56 nm) were also heated by a field of 9.4 kA/m at 198 kHz and gave an SAR value of 82.6 W/g [8]. Another study on 35 nm manganese ferrite nanoparticles of concentration 3 mg/mL at a field intensity of 350 G and a frequency of 765.95 kHz showed that the particles gave an SAR value of 70 W/g [74], while Muhammad Nauman et al studied gadolinium silicide nanoparticles and calculated an SAR value of 3.7 W/g for 43 nm particles at a field of 171 Oe and a frequency of 327 kHz [75]. Finally, a recent study using nanoparticles of different diameters based on La-Sr manganites, and with a low Curie temperature, gave SAR values ranging from 5.6 to 30 W/g [70].…”
Section: Assessment Of Sarmentioning
confidence: 99%
“…Substantial differences of properties of the magnetic nanoparticles (MNPs) from their bulk analogs and uniqueness of the MNP characteristics are of huge interest of researchers both in terms of fundamental studies of the magnetic nanoparticles [1][2][3][4] and practical applications (see, for example,the paper [5] and references therein), including usage in various biomedicine fields [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%